HUBUNGAN FREKUENSI BABY SPA DENGAN KUALITAS TIDUR BAYI USIA 3-6 BULAN - Ratna Widhiastuti; Wisnu Widyantoro; Ulfi Yuliani (Jurnal EDUNursing, 2022)
Sleep is a problem that is often complained of in infants under one year of age. But the problem experienced is that the baby has difficulty sleeping at night and if not treated seriously there is a behavior disorder. With good quality sleep, baby's growth can be achieved optimally. One way to meet these needs is a baby spa. The purpose of this study was to determine the relationship between the frequency of baby spas and the sleep quality of infants aged 3-6 months. This study uses a descriptive correlation with a cross-sectional approach. The research sample amounted to 48 respondents with a total sampling technique of sampling. The research instrument used a checklist sheet and a questionnaire. Data processing using Kendall's Tau statistical test. The results showed that the frequency of baby spas was mostly carried out routinely, namely 25 respondents (52.1%), the quality of baby sleep showed that most of them had good sleep quality, namely 21 respondents (43.8%). The results of statistical tests using Kendall's Tau obtained the results of the p-value 0.000<0.01. These results show that there is a relationship between the frequency of baby spas and the sleep quality of babies aged 3-6 months in Pasarbatang Village, Brebes Regency. Keywords: Frequency baby spa, Sleep quality, Infant.